Brand Bundling as a New Product Introduction Strategy : A Conceptual Framework - Singh, Sweta; Venugopal Rao, K. S. (Indian Journal of Marketing, 2017)
Bundling can be defined as a combination of two or more products or services into a single offering sold at a single selling price. While introducing a new product in the market, the manufacturer can launch the product by its own or can promote through bundling with an existing product under a different brand name to leverage the brand equity of the strong brand. Prior research in bundling asÂ a new product introduction strategy primarily focused upon the role of functional attributes on consumers' evaluation of the bundle. However, in the context of brand extension and co-branding literature, it was inferred that in addition to the functional benefits, brands also provide symbolic benefits to the consumers, and studying symbolic aspects of this strategy is very essential. Therefore, the objective of the paper was to develop and propose a model that studied the roles of symbolic (self-congruity) and functional (functional congruity) benefits on consumers' bundle purchase intention when bundling was used as a new-product introduction strategy. This study will help marketers to select their partners when they propose to use bundling as a new product introduction strategy.